Álláskeresők vállalkozóvá válását elősegítő támogatások Magyarországon 2011-2014. - Pápai Zsuzsanna (2015)
I have examined the assistance of transfer the place-hunter to entrepreneurship in Hungary between 2011 and 2014 in my thesis. I have presented the most popular assistance forms in detail. I would like to show in my thesis, that these kinds of tools such become an entrepreneur programs are ineffective, and worth the work to examine the invested money in this sector. I sent a questionnaire several central work offices in different country, but some of them didn’t send back to me the result on deadline. So, I can’t use this questionnaire, because you can make the examination only on the view of the full picture. I can get the most important data in my workplace. In the National Work Office, where I work, I got this information. Every central work office must send this information to the National Work Office. The detail examination of year 2011 I found that my assumption was wrong. After 180 day of the end of the assistance the examination and monitoring tests show that most of the participant had some job. This is very height ratio among the other methods. In 2011 this ratio was 71,25% (3251 person). In 2013 this ratio was 72,91%. In the examination would be nice to invite the participant and ask them, how they feel, what they did, how useful was the education and the assistance. With this information we can define the correlations, the cause and effect forces. Between the condition to start a venture, it would be necessary to examine that the potential entrepreneur has the knowledge, has the skills to start a company any maintain it. With the education and with the required business plan the life show that this company can be stay alive in the market even without the assistance. This is why I think this kind of projects in Békés and Baranya are very good idea. The projects is the local area can be very successful and a good proof of the assistance system. It would be useful to expand the research also some sociology parameters but unfortunately these are not the scope in this thesis. It would be useful to see how the parameters affect the different assistance method in different country. Also would be nice to examine some of the older but similar assistance. We could do some interview and make some typical carrier and life effect.